The perceived scope of internal audit function in Libyan public enterprises. Issue 6 (6th July 2015) - Abuazza, Wahid Omar; Mihret, Dessalegn Getie; James, Kieran; Best, Peter
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The aim of this exploratory study is to examine the perceptions of stakeholders regarding the scope of internal audit (IA) work in Libyan state-owned enterprises. Design/methodology/approach – Data were gathered through semi-structured interviews with chief executive officers, IA directors, administrative affairs managers, financial affairs managers and external auditors, which were supplemented with a review of relevant documentary evidence. Findings – The results of the study show that the scope of IA in Libyan organizations may not be sufficiently wide ranging to be considered as a value-adding service. The scope of the IA function may need to be expanded to cover a broader range of organizational functions if internal auditors are to offer value-adding services to their stakeholders. Practical implications – The IA profession has received scant attention in the literature, especially in the context of developing countries such as Libya. Therefore, such settings offer the potential to enhance the understanding of IA practices. As a study on a developing economy, it enhances understanding of the IA profession's global configuration beyond the predominantly market-driven, industrialized Western economies. Originality/value – In contrast to most previous studies, this study covers a broad range of IA stakeholders' views on the role of internal auditors. This coverage enabled an in-depth investigation of the factors affecting IA scope and understanding of stakeholder perceptions on the IA function.